2012
DOI: 10.1016/j.jvs.2011.10.121
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the bell-bottom technique vs hypogastric exclusion for the treatment of aneurysmal extension to the iliac bifurcation

Abstract: Introduction A significant proportion of patients undergoing endovascular aneurysm repair (EVAR) have common iliac artery aneurysms (CIAA). Aneurysmal involvement at the iliac bifurcation potentially undermines long-term durability. Methods Patients who underwent EVAR with CIAA were identified in two teaching hospitals. Bell-bottom technique (iliac limb ≥ 20mm) (BBT) or internal iliac artery embolization and limb extension to the external iliac artery (IIE+EE) were used. Outcome between these two approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 39 publications
3
35
0
2
Order By: Relevance
“…27 Earlier studies assessing the feasibility of the bell-bottom technique included larger caliber vessels in their cohorts, but the numbers are very small and the follow-up is short. 6,20,28 Naughton et al 19 published a series on the management of aCIA LZs using either bell-bottom or flared limb techniques compared with IIA embolization with distal external iliac artery LZ extension. These authors demonstrated that there was no significant difference in type Ib endoleak or iliac limb patency; in fact, the overall rate of complications and reintervention was lower in the bell-bottom group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Earlier studies assessing the feasibility of the bell-bottom technique included larger caliber vessels in their cohorts, but the numbers are very small and the follow-up is short. 6,20,28 Naughton et al 19 published a series on the management of aCIA LZs using either bell-bottom or flared limb techniques compared with IIA embolization with distal external iliac artery LZ extension. These authors demonstrated that there was no significant difference in type Ib endoleak or iliac limb patency; in fact, the overall rate of complications and reintervention was lower in the bell-bottom group.…”
Section: Discussionmentioning
confidence: 99%
“…If a bell-bottom 19 or flared stent-graft limb technique was employed, patients received either a flared limb from the manufacturer of the main body stent-graft, an aortic extension cuff, or an aortouni-iliac conversion device using methods previously described. 17,19,20 All overlapping graft segments were molded with a compliant balloon, and completion digital subtraction angiography was obtained to Postoperative CT surveillance with arterial and delayedphase venous imaging was typically obtained at 1, 6, and 12 months and annually thereafter unless radiographic findings dictated otherwise. Timing and need for any reintervention was based on the attending surgeon's judgment.…”
Section: Evar Proceduresmentioning
confidence: 99%
“…Th is meant occluding the ipsilateral IIA (with a plug or coils) and extending the end of the endograft into the EIA ( 5 ). Th is type of approach has been referred to as occlude and extend ( 14 ). Unfortunately, this leaves a signifi cant number of patients with limiting buttock claudication.…”
Section: Discussionmentioning
confidence: 99%
“…Th e limitations of this technique are that the iliac artery cannot be larger than 32 mm and that an adequate length of CIA must be available to accommodate the devices needed and allow for seal. Th e advantage of the bell-bottom technique versus exclude and extend is a lower complication rate of 6% vs 38% ( 14 ). However, the bell-bottom technique has also been shown to lead to a higher incidence of reintervention in the follow-up period (14% vs 2%) ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Torsello et al reported their 5-year data on bell-bottom extensions in 89 patients showing no change in CIAA diameter at last follow-up (18). When compared with embolization of the HA and extension of the endograft into the EIA versus placement of a bell-bottom graft, the combined incidence of perioperative complications and reintervention favors bell-bottom treatment (19).…”
Section: Tube Grafts and Bell-bottomsmentioning
confidence: 99%